العامة والحملة الفرنسية على مصر من كتابة ذكر تملك جمهور الفرنساوية الأقطار المصرية والبلاد الشامية للمعلم نقولا الترك - العزام صبحي (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
رغم كثرة ما كُتب عن الحملة الفرنسية من مؤلفات عربية-وغربية، عُرضت فيها دوافع الحملة ومجرياتها وآثارها على مصر خاصةً والمشرق العربي عامةً، إلا أنّ بعض الجوانب فيها تحتاج إلى مزيد من البحث والتقصّي، وكان من الموضوعات التي حظيت باهتمامي، العامة في مصر وموقفها من الحملة الفرنسية، وقد اعتمدت في تقصي هذا الموقف على مصادر إسلامية وغربية وذلك لبيان وجهات النظر المختلفة فيه. وقد قدّم البحث نبذة عن حياة المؤلف، وهو مؤلف معاصر لأحداث الحملة وشاهد عيان عليها، ثم عرض البحث موقف العامة من الحملة منذ نزولها في بندر الإسكندرية إلى أن وصلت إلى القاهرة، وبعد السيطرة على القاهرة عرض حركة المقاومة التي أبدتها الأقاليم المصرية الأخرى للمحتل الفرنسي، بحيثُ لم تخضع للمحتل بالسهولة التي كان يتوقعها، وقدّم معلومات وافية عن ثورة القاهرة، تلك الثورة التي قامت بها العامة وأذهلت المحتل، بحيث جعلته يعيد سياسته في التعامل مع المجتمع المصري، وبيّن الثورات التي قامت بها العامة في الأقاليم مستغلّةً غياب نابليون في غزو بلاد الشام، وعودته مهزوماً من تلك الأقاليم الشامية، وأوضح المشاعر التي عمت العامة بقدوم الحملة العثمانية لإنقاذ مصر من المحتل، والموقف الذي وقفته العامة إلى جانب القوات العثمانية عند دخولها القاهرة، أو في التصدي للفرنسيين من العودة إلى القاهرة ثانيةً. رغم الحرائق التي أصابت أحياء القاهرة، والموت الذي عصف بكثير من السكان بتلك الأحداث، وأخيراً أوضح الفرح الغامر الذي عمّ الناس بالاتفاق العثماني الفرنسي، والذي تضمن خروج الفرنسيين من مصر وعودة مصر ثانيةً إلى الدولة العلية. In spite of the presence of many Arabic and Western books written on the French crusade, showing causes, events and effects on Egyptian people and on the entire Arab nation, there are some aspects that need more research and inspection. One of the studies that attract my attention is the public in Egypt and their stand towards the French crusade. I depended on inspecting this stand from Islamic and western resources to show the different points of view from both sides. This research is a brief account about the author, he has grown up along with the crusade and Witnessed its events. The research presented the public stand from the crusade since it landed in Alexandria port till it reached Cairo. The research showed the resistant movement of the other Egyptian regions against the French occupiers. The Egyptian regions were not occupied easily as expected by the occupiers. The research presents complete information about Cairo revolution that was taken by the public people, which terrified the occupiers, compelling them to change their policy towards the Egyptians. The research showed the absence of Napoleon while he was attacking Sham area. He returned back defeated from Sham region. The research showed the feeling the people had when the Ottoman came to save Egypt from the occupiers and the stands of the public supporting Ottoman forces when entered Cairo or in defending French from coming back to Cairo in spite of the fires burning Cairo colonies and the terrifying deaths. Finally, the research showed the people great happiness to the agreement between the Ottomans and the French which implied the French departure from Egypt and the retuning of Egypt back to Higher State of the Ottomans.